Quality of the medical research article; whose responsibility? A necessary enquiry - Sathian, Brijesh; Roy, Bedanta; Banerjee, Indrajit (Journal of Biomedical Sciences, 2016)
No abstract. J. Biomed. Sci. 2015, 2(3):19-20.